Hubungan Derajat Akne Vulgaris dengan Kepatuhan Pengobatan pada Mahasiswa di Fakultas Kedokteran Universitas Riau - Alida Widiawaty; Zahtamal Zahtamal; Normalina Sandora; Amelinda Amelinda; Mugen Adi Suryo; Sysca Priastiwi (Jurnal Ilmu Kedokteran, 2018)
Successful treatment of acne vulgaris (AV) can impact patient’s quality of life. AV treatment outcome is associated with the patient adherence. The aim of this study was to know the association between acne vulgaris and adherence among medical students of Universitas Riau. The samples were students with AV according to inclusion criteria as 39 respondents. In this study, respondents got check the grade of the AV according to Lehmann classification, the adherence was measured using the translation and modification of Elaboration d’un outil d’evaluation de l’observance des traitements medicamenteux (ECOB) Questionnaire that has been tested. In this study, mild AV was found among 69.23% of the respondents as the most AV grade found among the respondents. Adherence rate was found to be poor as 53.85% of the respondents have poor adherence to medication. Statistic test showed there was a correlation between AV grade and adherence with the p-value of 0,006 (p<0,05).